2011
DOI: 10.22610/jebs.v3i2.265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Leadership Style on Organization Commitment: In A Mediating Role of Employee Values

Abstract: This paper aims to how leadership ship style effects the organization commitment of the employees, when the organization culture is reflecting the employee’s values in the organization. This paper is a conceptual based paper which gives theoretical evidence to support the idea. The paper also gives a brief overview of transactional leadership and transformational leadership. The results of the paper suggest that the leadership style is a strong dimension of organization commitment when organization culture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 19 publications
2
15
0
11
Order By: Relevance
“…Theoretically Hofstede (1984) and Schein (1997) identified that culture as software of the mind can be impacted by leadership style. This study is consistent with several researches by Bass (2000) and Sabir et al (2011), both found that leadership style impacts on culture, and leadership style changes as the culture of the organization changes. Agarwal et al (1999) stated that attention (as a vital component of servant leadership) has a positive relationship with organizational commitment, while Subramaniam (2011) proved that there was a relationship between servant leadership and organizational commitment.…”
Section: Figure 2: the Results Of Inner Model Direct Testingsupporting
confidence: 93%
See 1 more Smart Citation
“…Theoretically Hofstede (1984) and Schein (1997) identified that culture as software of the mind can be impacted by leadership style. This study is consistent with several researches by Bass (2000) and Sabir et al (2011), both found that leadership style impacts on culture, and leadership style changes as the culture of the organization changes. Agarwal et al (1999) stated that attention (as a vital component of servant leadership) has a positive relationship with organizational commitment, while Subramaniam (2011) proved that there was a relationship between servant leadership and organizational commitment.…”
Section: Figure 2: the Results Of Inner Model Direct Testingsupporting
confidence: 93%
“…Further, Werner (2000) postulates that the organizational culture influences on the extent to which employees are engaged in contextual performance which is defined as "individual efforts that are not directly related to their main task functions but are important because they shape the organizational, social, and psychological context that serves as the critical catalyst for task activities and processes". Sabir et al (2011) gave the model provides link between leadership style, organization culture, and organization commitment, and recommended that future research can be conducted with new variable i.e. servant leadership style in the model by replacing the transactional leadership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this context, it is the leadership's responsibility to determine that goal. In elaborating the effectiveness of organizational commitment, Sabir et al (42) stated that the chairman's leadership style has a strong relationship with each dimension of commitment. This relationship exists when employees felt that they have value in an organization.…”
Section: Commitment Roles In Employee Relations Between Leadership Anmentioning
confidence: 99%
“…Keuntungan lain yang akan didapat pada seseorang yang memiliki komitmen organisasi tinggi adalah meningkatnya kreatifitas seseorang terhadap organisasi (Carlos dan Filip, 2011 dalam Sabir et al, 2011). Tentu akan sangat bermanfaat manakala seorang pengurus pondok pesantren yang sudah memiliki intensi positif sejak awal, kemudian ditingkatkan derajat komitmennya terhadap organisasi sehingga kreatifitas untuk mengelola sebuah pesantren akan lebih tajam.…”
Section: Pendahuluanunclassified
“…Temuan beberapa faktor eksternal yang berpengaruh terhadap komitmen organisasi antara lain: job characteristics (Haryanto & Sriwidodo, 2009;Djastuti, 2011), kualitas kehidupan kerja (Maharani, 2012), job environment (Maharani, 2012), gaya kepemimpinan (Gao & Bai, 2011;Sabir, 2011), budaya organisasi (Sabir, 2011), hubungan interpersonal (Leiter & Maslach, 1988;Puspitasari & Asyanti, 2011).…”
Section: Komitmen Organisasiunclassified